Guaiane sesquiterpenes from the gorgonian Echinogorgia flora collected in the South China Sea. Issue 5 (19th January 2022) - Luo, Xiangchao; Wu, Rongcui; Han, Xiao; Tang, Xuli; Wang, Qi; Li, Pinglin; Li, Guoqiang
Abstract : Echinoflorine (1 ), a new dimethylamino-substituted guaipyridine alkaloid with a novel γ-lactone-cyclohepta[ c ]pyridine fused skeleton, and three new guaiane sesquiterpene lactones, echinofloranolides A–C (2–4 ), together with eight known guaiane sesquiterpenes were isolated from the gorgonian Echinogorgia flora collected in the South China Sea. Abstract : Echinoflorine (1 ), a new dimethylamino-substituted guaipyridine alkaloid with a novel γ-lactone-cyclohepta[ c ]pyridine fused skeleton, and three new guaiane sesquiterpene lactones, echinofloranolides A–C (2–4 ), together with eight known guaiane sesquiterpenes were isolated from the gorgonian Echinogorgia flora collected in the South China Sea. Their structures were elucidated by 1D and 2D NMR, HRESIMS, calculated ECD and DP4+ probability analyses.